2021
DOI: 10.13057/biodiv/d220407
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcode of Enggano hill myna, Gracula religiosa enganensis (Aves: Sturnidae) based on mitochondrial DNA cytochrome oxidase subunit I

Abstract: Abstract. Jarulis, Muslim C, Kamilah SN, Utama AF, Permana D, Sari MM, Prayitno AH, Jannah IM. 2021. DNA barcode of Enggano hill myna, Gracula religiosa enganensis (Aves: Sturnidae) based on mitochondrial DNA cytochrome oxidase subunit I. Biodiversitas 22: 1635-1643. The sharp decline of the Enggano hill myna population due to illegal trading and habitat degradation needs to be our concern to prevent this bird from extinction. Taxonomically, Enggano hill myna is referred to as a sub-species, but this has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The genetic distances that we discovered are nearly identical to those identified in prior DNA barcoding investigations (Astuti & Sulandari, 2010;Huang & Tu, 2016). According to Jarulis et al (2021), the average genetic distance between individuals in the Enggano hill myna population was 0.3%, while the average genetic distance between hornbill populations was 0.2-0.8% (Jarulis et al, 2018). Many biosystematists have utilized the genetic distance between populations to identify the taxonomic position of an animal taxon.…”
Section: Genetic Distancesupporting
confidence: 80%
See 4 more Smart Citations
“…The genetic distances that we discovered are nearly identical to those identified in prior DNA barcoding investigations (Astuti & Sulandari, 2010;Huang & Tu, 2016). According to Jarulis et al (2021), the average genetic distance between individuals in the Enggano hill myna population was 0.3%, while the average genetic distance between hornbill populations was 0.2-0.8% (Jarulis et al, 2018). Many biosystematists have utilized the genetic distance between populations to identify the taxonomic position of an animal taxon.…”
Section: Genetic Distancesupporting
confidence: 80%
“…According to Hebert et al (2003b), Vilaca et al (2006, and Efe et al (2009), the dissimilarity threshold between animal species is typically greater than 3.0%. Similarity values for Gracula religiosa enganensis ranged between 98.83% and 99.83% (Jarulis et al, 2021). Johnsen et al (2010) revealed that the similarity value of Scandinavian birds exceeded 97.0%.…”
Section: Coi Gene Sequence Lengthmentioning
confidence: 96%
See 3 more Smart Citations